EU global health policy: An agenda for the German Council Presidency - Susan Bergner; Maike Voss (Stiftung Wissenschaft und Politik (SWP), 2020)
In the second half of 2020, Germany will take over the Council Presidency of the European Union. It will form a presidency trio with Portugal and Slovenia, who will succeed Germany in 2021. The Federal Government should use its presidency to strengthen the EU's role in global health policy. The EU has so far focused primarily on (infectious) disease prevention and control as it has most recently in response to the coronavirus outbreak (Covid-19). However, in order to contribute to the United Nations' Sustainable Development Goals, it should focus more comprehensively on health systems. This would require an intersectoral and preventive approach at EU level, opening the door to coherent collaboration, alliances and a people-centered policy in line with European values.
Keywords: 320